A Majestic Burden: Discovering the Untold Stories of Congressional Black Caucus (CBC) Women and Learning Through Narrative Analysis8 - Elice E. Rogers (Adult Education Research Conference, 2006)
The purpose of this completed research investigation is to articulate three of four final research findings as part of a larger study that investigated diverse leadership among an under-represented group and to extend current research on African American women political leaders.
Keywords: Leadership; African American women